Respostas
respondido por:
0
3x - 1/4 = 2 (4)
12x - 4/4 = 8
12x - 1 = 8
12x= 8 + 1
12x = 9
x = 9/12 ÷3
x = 3/4
12x - 4/4 = 8
12x - 1 = 8
12x= 8 + 1
12x = 9
x = 9/12 ÷3
x = 3/4
respondido por:
0
Oi
3x-1:4=2
3x-4/1 =2 ==>O mmc de1,4,1=4
12x-4/4=8
12x-1=8
12x=8+1
12x=9
x=9/12==>simplifica por 3
x = 3/4
Espero ter ajudado
3x-1:4=2
3x-4/1 =2 ==>O mmc de1,4,1=4
12x-4/4=8
12x-1=8
12x=8+1
12x=9
x=9/12==>simplifica por 3
x = 3/4
Espero ter ajudado
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás